2003
DOI: 10.1097/01.ta.0000053396.02126.cd
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Paramedic Rapid Sequence Intubation on Outcome in Patients with Severe Traumatic Brain Injury

Abstract: Paramedic RSI protocols to facilitate intubation of head-injured patients were associated with an increase in mortality and decrease in good outcomes versus matched historical controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
187
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 333 publications
(197 citation statements)
references
References 21 publications
3
187
0
7
Order By: Relevance
“…In five studies, 30 32 -35 the frequency of different procedure failures or complications during airway management were reported. With pre-hospital intubation, intubation failure or complication rates ranged from 2.1% 30 to 41.1% 35 (Table 4). Two reports 30 34 included absolute numbers of intubation failures in the pre-hospital and in-hospital period; study results were inconclusive (Fig.…”
Section: Harm Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…In five studies, 30 32 -35 the frequency of different procedure failures or complications during airway management were reported. With pre-hospital intubation, intubation failure or complication rates ranged from 2.1% 30 to 41.1% 35 (Table 4). Two reports 30 34 included absolute numbers of intubation failures in the pre-hospital and in-hospital period; study results were inconclusive (Fig.…”
Section: Harm Outcomesmentioning
confidence: 99%
“…5). Three studies 7 30 36 reported on pneumonia after pre-hospital or in-hospital intubation; it was the primary study outcome in In-hospital mortality Suominen and colleagues 29 Sloane and colleagues 30 Winchell and colleagues 31 Gausche and colleagues 32 Murray and colleagues 33 Cooper and colleagues 34 Davis and colleagues 35 Bochicchio and colleagues 36 DiRusso and colleagues 37 Wang and colleagues 38 Davis and colleagues 39 Davis and colleagues 28 Klemen and Grmec 40 1 h mortality von Elm et al …”
Section: Harm Outcomesmentioning
confidence: 99%
See 3 more Smart Citations